Pengembangan Keterampilan Digital Siswa MAN 2 Jepara Melalui Pelatihan HTML - Ahmad Faidlon; Muhammad Miftakhul Ulum; Muhammad Nabil Mas’ud; Shiva Fauziyah; Mila Ati Azka (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
This article discusses the implementation of HTML training at MAN 2 Jepara as part of a community service initiative by the UNISNU KKN team in Kelet Village to develop students' digital skills. Through this article, we will explain the training implementation methods, the objectives to be achieved, and the expected benefits. Currently, students from MAN 2 Jepara majoring in informatics have learned how to use computers, especially Microsoft Word and Microsoft Excel. As a major with an informatics background, there is certainly an expectation to learn other things in the field, especially in web development. Therefore, the UNISNU KKN team in Kelet Village took the initiative to conduct basic HTML training. To achieve the expected goals and benefits, the author adopts practical and interactive training methods. The training results show an increase in understanding of the basic concepts of HTML by 43%, interest in the field of web development by 28%, and active participation in question and answer sessions by 50%.